Efecto antibacteriano in vitro de miel de abejas (apis mellifera) en cepas de streptococcus mutans. - Pasco Olguín, Gary Alexánder (2010)
The study had as objectives it decides the minimum inhibitory concentration (CMI) and the minimum bactericide concentration (CMB) of the honey of bees in stumps to standardize of Streptococcus mutans (ATCC35668). To carry out investigation happiness, it face the stumps of Streptococcus mutans with the honey of bees to different concentrations (from 1 % to 7%), by means of the method of turbidimeter in tube with tioglicolato broth, for the minimum concentration inhibitory and for growth in plate in soya tripticasa agar for the minimum bactericide concentration . It concludes in the following: The minimum inhibitory concentration (CMI) of the honey of bees in stumps of Streptococcus mutans is of 5.5 % and the minimum bactericide concentration (CMB) of the honey of bees in stumps of Streptococcus mutans is of 7 %